Opera and the Great Reform Act: Silver Fork Fiction, 1822-1842 - Copeland, Edward (Romanticism on the Net, 2004)
AbstractIn the years leading up to and away from the Reform Act of 1832, opera and politics came into alignment for writers of silver fork fiction, particularly Catherine Gore and Lady Charlotte Bury. The King’s Theatre in the Haymarket, the home of Italian opera in London, provided them with a politically charged public space for women, one of the few available, in which they could examine the consequences of political reform on women’s lives, particularly the conflicts faced by aristocratic women before the irresistible force of middleclass social mores. Through the King’s Theatre with its stairs, corridors, boxes, and class-differentiated spaces, the silver fork novelists track the consequences of Whig politics. Employing Italian opera as a national trope both for its aristocratic associations and its symbolic plots, Gore and Bury mount a probing assessment of contemporary political change through a fusion of fashion and politics.